Use of microbiota balancing additives in commercial poultry feed: Review (Research, Society and Development, 2021)
The microbiota balancing antibiotics have been used in animal feed since the 50's, by promoting health benefits to animals, however, the prolonged use of these additives triggered the problem of bacterial resistance, which led the world and national bodies (WHO, EU, FDA and MAPA) to ban various additives. However, birds in industrial systems are subjected to dense and challenged environments, making it impossible to exempt compounds in the diet that modulate the intestinal microbiota and consequently beneficially favor the digestibility and absorption of nutrients in the diet. In this aspect, the use of microbiota balancing additives alternative to antibiotics, such as prebiotics, probiotics and symbiotics, become indispensable because they are natural, do not cause bacterial resistance and promote mutual benefits to animal health. Thus, this review elucidates the benefits of microbiota balancing additives in feeding commercial laying birds, with emphasis on the effects produced from the modulation of the resident microbiota. The methodology adopted was a descriptive study, resulting in a literature review based on worldwide scientific articles.